Community-Based Education on the Mitigation of Religious Radicalism among Urban Muslim Communities - Hanik Yuni Alfiyah; Ali Mas'ud; Syaifuddin Syaifuddin; Muhammad Fahmi; Ulul Azmi Nur Rohmatullah (GUYUB: Journal of Community Engagement, 2026)
This community service program is motivated by the increasing vulnerability of urban Muslim communities to religious radicalism, particularly influenced by digital media that promotes exclusive and intolerant narratives. Therefore, a participatory and community-based intervention is urgently needed. This program employs a Participatory Action Research (PAR) approach, involving the community actively through stages of problem identification, planning, action, observation, reflection, and evaluation. Data were collected through observation, interviews, documentation, and pretest–posttest instruments, and analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing. The results demonstrate measurable improvements in participants’ understanding, attitudes, and behaviors regarding radicalism. Quantitatively, rejection of radical ideas increased from 67.7% in the pretest to 93.25% in the posttest in the cognitive domain. Similarly, anti-radical attitudes increased significantly to 97.5%, while the tendency toward radical thinking decreased from a score of 32.2 to 6.7. The impact of this program is reflected in enhanced religious moderation literacy, increased openness to dialogue, and improved community readiness to develop environment-based preventive strategies. Furthermore, the program strengthens social resilience and collective awareness, positioning community-based participatory education as an effective and sustainable model for mitigating religious radicalism in urban settings.